Cultural Response of The Aboge Islamic Group to The Puritanism Movement - Azizah, Intan Nur (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2022)
The puritanism movement began in the 19th century, but a response to this event only emerged in the early 20th century, with the emergence of various puritan organizations. Since then, the spread of puritanism has reached rural areas, where the people are so strong in maintaining the Kejawen tradition. The Aboge Islamic Society is one of the Islamic groups that are still very strong with Javanese-Islamic nuances. Aboge's calculations in determining religious holidays and certain traditional celebrations are one of the social assets owned. This study aims to analyze in a cultural context, what are the strategies of the Aboge people in maintaining their identity when facing the penetration of the Puritan Islamic movement. This research is a type of qualitative research by not rule out quantitative data. This study uses ethnographic methods. The ethnographic method tries to describe the real conditions that exist in the field using participatory observation methods combined with interviews and even quantitative surveys, while on the other hand ethnography as a product tries to carry out cultural analysis only "behind the desk" as an observer. The results of the study show that the cultural response given by the Aboge community to the puritanism movement is an attempt to maintain the identity and existence of the Aboge group. Several responses were made, 1) the emergence of the Nyandi Islamic and Nyantri Islamic groups within the Aboge group as a form of change shown as a consequence of the times, besides that this was also the influence of the existence of the puritanism movement. 2) the use of the Aboge calendar. Calculations using the Aboge calendar to determine religious holidays are a characteristic of the Aboge community and this is used as social capital to maintain their existence in society. 3) Javanese petungan. The form of syncretism that is still held by the Aboge people which later gave birth to the Javanese petungan system based on weton includes determining when to build a house, when to travel or other matters. 4) the use of Jiping and Turki methods in the Islamic religious teaching system. Jiping or Koran Ears made the Aboge group not study texts, they only listened to the studies delivered by the Aboge elders. Likewise, Turki or tutur kaki also have the same concept, although in its development the Nyantri Islamic group has started using texts in studying religion